Restoration, reclamation, and rehabilitation: on the need for, and positing a definition of, ecological reclamation. Issue 7 (7th July 2021) - Gerwing, Travis G.; Hawkes, Virgil C.; Gann, George D.; Murphy, Stephen D.
Abstract : Within the burgeoning field of restoration ecology, defining the concept of reclamation relative to rehabilitation and ecological restoration is important to enhance comparability between studies, as well as to enable clear communication of project specific methods and goals. The Society for Ecological Restoration's international standards (SER Standards), second edition, defines reclamation as "the process of making severely degraded land fit for cultivation or a state suitable for some human use." However, we posit that this definition, and its anthropogenic focus, does not well match how the term is often used by practitioners, and in some legal or agency documents. Further, the relationship between restoration, rehabilitation, and reclamation is unclear. We propose a more specific term and definition, ecological reclamation: "the process of assisting the recovery of severely degraded ecosystems to benefit native biota through the establishment of habitats, populations, communities, or ecosystems that are similar, but not necessarily identical to surrounding and naturally occurring ecosystems." This definition emphasizes that the objective of a reclamation project may not be direct human use, and begins to better distinguish between ecological reclamation, rehabilitation, and ecological restoration; however, more work and discussion on these relationships is required. Distinguishing these terms will result in better comparisons between studies, improving current and future literature reviews. Further, this term will also enable practitioners to better define project goals, and enhance communication to stakeholders, practitioners, and researchers.